Dietary inclusion of green tea (Camellia sinensis) leaf flour enhances growth and affects hematological parameters in Nile Tilapia (Oreochromis niloticus) - Wahab, Gunawan Abdul; Salwadiva, Jihan Fathia; Putra, Dedi Fazriansyah; Irwan, Irwan (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
Nile tilapia (Oreochromis niloticus) is an important aquaculture species due to its fast growth and high economic value, with feed quality being a key factor in production efficiency. This study evaluated the effects of dietary green tea (Camellia sinensis) leaf flour on growth performance, hematological parameters, and intestinal histology of Nile tilapia. A completely randomized design was applied with six dietary treatments (02.5 g/kg feed) and three replicates each. Supplementation at 1.5 g/kg produced the best growth response, with significant improvements (P 0.05) in weight gain (7.24 0.91 g), length gain (3.61 0.21 cm), and specific growth rate (2.67 0.20%/day), while feed conversion ratio, feed efficiency, and survival did not differ among treatments. Hematological values varied but remained within normal physiological ranges. Histological analysis indicated enhanced villi morphology, suggesting improved nutrient absorption. The bioactive properties of C. sinensis highlight its potential as a functional feed additive to improve tilapia growth and health, offering practical applications for sustainable aquaculture.Keywords:TilapiaGreen tea leaf flourFish growth performanceHematological parametersFeed additiveRasakan sensasi serunya bermain tanpa hambatan di situs link gacorqq, kesempatan mendapatkan jackpotnya cukup mudah dan sangat cepat.